2003
DOI: 10.1007/bf03256650
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nuclear Factor Kappa B in the Pathogenesis of Pulmonary Diseases: Implications for Therapy

Abstract: The nuclear factor kappa B (NF-kappaB) transcription factor plays a key role in the induction of pro-inflammatory gene expression, leading to the synthesis of cytokines, adhesion molecules, chemokines, growth factors and enzymes. Results of studies in in vitro and in vivo models of inflammation and malignancy have also suggested central roles for NF-kappaB in programmed cell death, or apoptosis. NF-kappaB plays a central role in a variety of acute and chronic inflammatory diseases. In the common lung diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(104 citation statements)
references
References 61 publications
3
96
0
2
Order By: Relevance
“…7). NF-κB, an important mediator of immune and inflammatory responses, has been strongly implicated in ALI (46)(47)(48)(49)(50)(51). Evidence supports the notion that NF-κB induces transcription of human and rat D2 gene expression, and, indeed, a potent NF-κB-binding site has been demonstrated in the human D2 gene (52,53).…”
Section: Discussionmentioning
confidence: 74%
“…7). NF-κB, an important mediator of immune and inflammatory responses, has been strongly implicated in ALI (46)(47)(48)(49)(50)(51). Evidence supports the notion that NF-κB induces transcription of human and rat D2 gene expression, and, indeed, a potent NF-κB-binding site has been demonstrated in the human D2 gene (52,53).…”
Section: Discussionmentioning
confidence: 74%
“…The transcription factor NF-kB, regulates the expression of a large number of inflammatory genes, is involved in the pathogenesis of ALI and is known as an important target for anti-inflammatory molecules (Wright & Christman, 2003). Under resting conditions, NF-kB is located in the cytoplasm bound to IkB.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil apoptosis, regulated by NFκB, plays a critical role in the resolution of inflammation associated with these disorders (28)(29)(30)(31)(32)49). Although studies have shown that NFκB is activated in patients with ALI, sepsis, and BPD (4,(30)(31)(32)(33)44), the stage of NFκB activation in these patients is not known. It seems plausible that it is the persistent NFκB activity, and not the early NFκB activation induced by neutrophil stimulation for 30 min, that is associated with the tissue injury in these inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activation of NFκB in neutrophils has been associated with the pathogenesis of ALI, BPD, sepsis, and other inflammatory diseases (28)(29)(30)(31)(32)(33). Whereas the acute NFκB activation induced by neutrophil stimulation for 30-60 min has been well documented (34)(35)(36)(37)(38)(39)(40)(41), NFκB activation during the prolonged neutrophil stimulation that is likely to occur in inflammatory disorders has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%